Southern Hemispheric nitrous oxide measurements obtained during 1987 airborne Antarctic ozone experiment - Loewenstein, M.; Strahan, S. E.; Chan, K. Roland; Podolske, J. R. (1988)
The chemical lifetime of N2O is about 150 years, which makes it an excellent dynamical tracer of air motion on the time scale of the ozone depletion event. For these reasons it was chosen to help test whether dynamical theories of ozone loss over Antarctica were plausible, particularly the theory that upwelling ozone-poor air from the troposphere was replacing ozone-rich stratospheric air. The N2O measurements were made with the Airborne Tunable Laser Absorption Spectrometer (ATLAS) aboard the NASA ER-2 aircraft. The detection technique involves measuring the diffential absorption of the IR laser radiation as it is rapidly scanned over an N2O absorption feature. For the AAOE mission, the instrument was capable of making measurements with a 1 ppb sensitivity, 1 second response time, over an altitude range of 10 to 20 kilometers. The AAOE mission consisted of a series of 12 flights from Punta Arenas (53S) into the polar vortex (approximately 72S) at which time a vertical profile from 65 to 45 km and back was performed. Comparison of the observed profiles inside the vortex with N2O profiles obtained by balloon flights during the austral summer showed that an overall subsidence had occurred during the winter of about 5 to 6 km. Also, over the course of the mission (mid-August to late September), no trend in the N2O vertical profile, either upward or downward, was discernible, eliminating the possibility that upwelling was the cause of the observed ozone decrease.